The health-saving culture formation among the students in the higher pedagogic education - Ardak Kalimoldayeva, Kamarsulu Ibrayeva, Talgat Yerezhepov; Zhanyl Madalieva, Ardak Kalimoldayeva, Menslu Djeksembekova; Abisheva, Onal (Opción, 2019)
The article considers the new pedagogic model that is aimed at the formation and development of the health-saving culture. To achieve this purpose, a complex of complementary research methods was used that included pedagogical experiment as the most significant one. As a result of the experiment, the new approach to the development of health-saving culture was elaborated. The students became more responsible in the issues that were associated with their health. As a conclusion, under the favorable social-pedagogical conditions, this system is able to become a stable factor that ensures the formation of health-saving culture among the students